Oscillation-Based Test Applied to a Wideband CCII. (24th May 2017) - Petrashin, Pablo; Toledo, Luis; Lancioni, Walter; Osuch, Piotr; Stander, Tinus
Abstract : Oscillation-based testing (OBT) has been proven to be a simple, yet effective VLSI test for numerous circuit types. This paper investigates, for the first time, the application of OBT verification for second generation current conveyors (CCIIs). The OBT is formed by connecting the CCII into a simple Wien bridge oscillator and monitoring both the amplitude and frequency of oscillation. The fault detection rate, taking into account both the open and short circuit fault simulation analyses, indicates 96.34% fault coverage using a combination of amplitude and frequency output sensing in all technology corners. The only nondetected faults are short circuits betweenV D D andV S S, which can be detected using other techniques such as IDDQ testing. This method is found to be sensitive to resistor and capacitor process variation in the Wien bridge oscillator, but mitigating test steps are proposed.